2023
DOI: 10.3389/fimmu.2023.1160301
|View full text |Cite
|
Sign up to set email alerts
|

Human IL-32θA94V mutant attenuates monocyte-endothelial adhesion by suppressing the expression of ICAM-1 and VCAM-1 via binding to cell surface receptor integrin αVβ3 and αVβ6 in TNF-α-stimulated HUVECs

Abstract: Interleukin-32 (IL-32), first reported in 2005, and its isoforms have been the subject of numerous studies investigating their functions in virus infection, cancer, and inflammation. IL-32θ, one of the IL-32 isoforms, has been shown to modulate cancer development and inflammatory responses. A recent study identified an IL-32θ mutant with a cytosine to thymine replacement at position 281 in breast cancer tissues. It means that alanine was also replaced to valine at position 94 in amino acid sequence (A94V). In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…22 Jae-Young Park et al demonstrated that FAK regulates the inflammatory response of vascular endothelial cells in inflammatory diseases such as slow-onset atherosclerosis. 31 Jin et al found that in diabetic cardiomyopathy, FAK is involved in regulating chronic inflammation in cardiomyocyte cardiomyocytes. 32 Therefore, FAK is an important regulator of inflammatory responses in a variety of metabolic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…22 Jae-Young Park et al demonstrated that FAK regulates the inflammatory response of vascular endothelial cells in inflammatory diseases such as slow-onset atherosclerosis. 31 Jin et al found that in diabetic cardiomyopathy, FAK is involved in regulating chronic inflammation in cardiomyocyte cardiomyocytes. 32 Therefore, FAK is an important regulator of inflammatory responses in a variety of metabolic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…β1and β2-integrins are expressed in high concentrations on monocytes in RA and participate in the adhesion of monocytes to activated endothelial cells. The β1 subfamily of integrins includes very late antigen-4 (α4β1) and -5 (α5β1) that bind to fibronectin and vascular cell adhesion molecule-1 in the endothelium and provoke monocyte adhesion [42]. β2-integrins take part in the formation of CD11 a,b,c (CD18) complexes in RA, which are mostly presented by CD11 b molecules and associated with the ligands in the endothelial lining.…”
Section: β1and β2-integrinsmentioning
confidence: 99%